AWARENESS AND KNOWLEDGE ABOUT VARIOUS DENTAL TREATMENTS AMONG ENGINEERING STUDENTS - S, Shreenidhi; Ganesh S, Balaji; Sivaswamy, Dr. Vinay (International Journal of Psychosocial Rehabilitation, 2019)
Engineering students belong to a large scale of educated and professional group of people who are prone more to stress and oral health related problems. This study is conducted in order to associate the level of awareness engineering students are of dental treatments and their extent of knowledge about implementing at need. To study the extent of awareness and knowledge about various dental treatments among engineering students. A set ofquestionnaires were prepared, developed and circulated among the engineering students in relation with the awareness and knowledge about various dental treatments. A total of 217 responses were collected and analysed. The results were compiled for analysis. The obtained results show that engineering students are widely aware about various dental treatments. The study concludes that of the growing and enhancement in technology, the extent of awareness and knowledge about various dental treatments among engineering students is quite good.